Kesiapan UMKM dalam Adopsi Teknologi untuk Mendukung Ekosistem Bisnis - Widianingsih, Rini; Fitrijati, Krisnhoe Rachmi; Suparlinah, Irianing; Ulfah, Permata; Pratiwi, Umi; Purwati, Atiek Sri; Sunarmo, Agus (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The evolution of digital technology demands that Micro, Small, and Medium Enterprises (MSMEs) adapt to survive and remain competitive in an increasingly complex business ecosystem. This community service article aims to enhance MSMEs’ readiness to adopt digital technology to support a sustainable business ecosystem. The implementation method involved outreach, training, and mentoring MSME actors focusing on accounting applications, digital marketing, and social media utilization. Through this approach, MSMEs were equipped with digital literacy, enhanced human resource competencies, and an understanding of relevant technologies. The results indicate that while most MSMEs are aware of the importance of digitalization, they continue to face obstacles in digital literacy, technical infrastructure, and organizational support. This community service effort is expected to serve as a strategic step in building a digital business ecosystem that is inclusive, adaptive, and sustainable for MSMEs.